From timber to medicine: value added for the forest sector through broadening the product portfolio - Österberg, Monika; Karjalainen, Markku; Lintunen, Jussi; Tammelin, Tekla; Asikainen, Antti; Vakkilainen, Esa; Toivonen, Ritva; Virta, Pasi; Henn, Alexander; Nuutinen, Emmi-Maria; Kohl, Johanna; Hassinen, Jukka (Metsäbiotalouden tiedepaneeli, 2024)
Forests are the foundation of Finland’s diverse well-being. The forest industry is one of the largest industrial sectors in Finland and plays an important role in Finland’s national economy. Finland’s bioeconomy strategy has set a target of doubling the value added of the bioeconomy by 2035 without compromising biodiversity and climate objectives. However, achieving all forest-related targets is difficult, and choices must be made. To support these choices, research-based analyses are needed to find an optimal balance between forest use, conservation and climate objectives. A discussion paper on the future of the forest sector published by the Natural Resources Institute Finland (Luke) in 2023 concluded that Finland has the potential to multiply forest-based value added, provided that the business environment can be made attractive for investments by domestic and international companies. In this report of the Finnish Forest Bioeconomy Science Panel, we continue this discussion. We look into the potential future product portfolio of the forest sector and the value added it can generate. The products considered have been divided into upgrades of existing solutions and new innovations. The new innovations include, for example, flexible packaging, product groups based on advanced specialty fibres and a broad range of lignin products. It is evident that a significant increase in forest harvesting is not sustainable. Thus, in the report we consider a scenario where value is added without increasing harvest volumes. According to this report, the key strategies for enhancing the value added of the forest sector include extending value chains in Finland and using side streams more effectively. An impactful approach to value addition in the foreseeable future involves advanced processing of timber into cross-laminated timber (CLT) or laminated veneer lumber (LVL), which could replace concrete in the construction of apartment building frames. In the future, achieving significant value added requires the commercialisation of new material innovations in Finland. For example, if a quarter of the exported pulp (1,000 kt) were refined into, for example, nanocellulose, textile fibres, special packaging and barrier materials, a value added of €3 billion could be achieved. The extensive processing of lignin into various products could lead to a value added of €1.5 billion. In this scenario, the total value added would increase by more than 80% compared to 2019 levels. This increase is significant, although not sufficient to double the value added. Substantial investments are essential to transform the existing product portfolio towards higher value-added products. Concurrently, investments in research and education are imperative. Finland must cultivate an operating environment that is appealing for both investments and skilled labour. While this report primarily focuses on economic considerations, it is crucial to acknowledge that forest-related choices are impacted by biodiversity and climate objectives. Thus, a holistic approach is necessary, integrating climate and restoration measures, as well as the advancement of the bioeconomy, to ensure that actions contribute optimally to all objectives. The aim of this report is to lay the ground for future scenario analyses. The figures and estimates herein are based on a number of assumptions; therefore, the findings should be regarded as indicative. Nevertheless, the calculations have been extended to the sectoral and national economy levels, aiming to provide a more comprehensive estimate of the economic significance of the new products and their production. As innovations progress and data on manufacturing costs and sales market prices emerge, these estimates can be further refined for greater accuracy. Policy recommendation of the Finnish Forest Bioeconomy Science Panel: • The bio-based industry has the potential to accelerate economic development in the European Union. EU policy should steer research and investments towards high value added bio-based industries. Uncertainty about the conditions to use forests in the EU, for example, is eroding the investment climate. A key factor contributing to uncertainty is the proliferation of EU regulation related to forests, with more than 70 fluctuating policy measures affecting forests. • Finland needs to become a more attractive environment for entrepreneurs and international talent. It is important that our university-educated masters, engineers, and doctorates find employment in Finland and integrate into Finnish society. • To support bio-based material innovations, funding is needed for applied multidisciplinary development to ensure, among other things, the technical and financial potential, sustainability and performance of new materials in different applications. • Wood should be used to make long-lasting and recyclable products that serve as carbon storage. Wood-based solutions can replace products with a higher carbon footprint than wood products, particularly in the construction sector. Wood and wood-based solutions should be integrated into education, industrial building frameworks and the policies that govern them. • Forests are more than a material bank for the bioeconomy. Decision-makers need to reconcile the sometimes-contradictory objectives of forest use, such as economic growth, climate, biodiversity and recreation.
Tämä julkaisu on saatavilla myös suomeksi.
Keywords: bioeconomy; forest industry; value added; lignin; nanocellulose; further processing; wood construction; wood products